2019
DOI: 10.1111/pbi.13188
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the genetic architecture of maize kernel size traits by combined linkage and association mapping

Abstract: SummaryKernel size‐related traits are the most direct traits correlating with grain yield. The genetic basis of three kernel traits of maize, kernel length (KL), kernel width (KW) and kernel thickness (KT), was investigated in an association panel and a biparental population. A total of 21 single nucleotide polymorphisms (SNPs) were detected to be most significantly (P < 2.25 × 10−6) associated with these three traits in the association panel under four environments. Furthermore, 50 quantitative trait loci (QT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 105 publications
5
66
1
Order By: Relevance
“…A significant overlap between the QTL identified in this study and grain size SNPs identified in rice (Huang et al , ) was observed, with 60% of the rice grain size SNPs identified within a 1‐cM window of the sorghum QTL identified in this study ( P ‐value < 0.05, chi‐square test), and with 80% of the rice grain size SNPs identified within 5 cM (Table S13). A similar trend was found when comparing with kernel size SNPs identified in maize (Liu et al , ), with 26% and 70% of maize kernel size SNPs identified within 1‐cM and 5‐cM window of sorghum QTL identified in this study (Table S13).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…A significant overlap between the QTL identified in this study and grain size SNPs identified in rice (Huang et al , ) was observed, with 60% of the rice grain size SNPs identified within a 1‐cM window of the sorghum QTL identified in this study ( P ‐value < 0.05, chi‐square test), and with 80% of the rice grain size SNPs identified within 5 cM (Table S13). A similar trend was found when comparing with kernel size SNPs identified in maize (Liu et al , ), with 26% and 70% of maize kernel size SNPs identified within 1‐cM and 5‐cM window of sorghum QTL identified in this study (Table S13).…”
Section: Resultssupporting
confidence: 88%
“…Sorghum shares close ancestry with maize and rice, with orthologous genes from these species commonly sharing the same function (Bolot et al , ; Paterson et al , ; Zhang et al , ). A significant association was found between the locations of the QTL in this study and GWAS signals for grain size in rice (Huang et al , ) and maize (Liu et al , ), and orthologous of cloned grain size genes from rice and maize. Both findings strongly support a common genetic architecture underlying this trait across these cereals.…”
Section: Discussionsupporting
confidence: 59%
“…A significant overlap between the QTL identified in this study and grain size SNPs identified 338 in rice (Huang et al, 2012) was observed, with 60% of the rice grain size SNPs identified 339 within a 1cM window of the sorghum QTL identified in this study (p-value<0.05, χ 2 test), 340 and with 85% of the rice grain size SNPs identified within 5 cM (Table S13). A similar trend 341 was found when comparing with kernel size SNPs identified in maize (Liu et al, 2019), with 342 30% and 70% of maize kernel size SNPs identified within 1 cM and 5 cM window of 343 sorghum QTL identified in this study (Table S13).…”
supporting
confidence: 74%
“…Sorghum shares close ancestry with maize and rice, with orthologous genes from these 495 species commonly sharing the same function (Bolot et al, 2009;Paterson et al, 1995). A 496 significant association was found between the locations of the QTL in this study and GWAS 497 signals for grain size in rice (Huang et al, 2012) and maize (Liu et al, 2019), and 498 orthologous of cloned grain size genes from rice and maize. Both findings strongly support a 499 common genetic architecture underlying this trait across these cereals.…”
Section: Correspondence Of Loci Controlling Grain Size Among Cereals 494mentioning
confidence: 62%
“…Genome‐wide association study (GWAS) is a powerful tool to dissect the genetic architecture of complex traits (Korte and Farlow ), overcome the limitations of QTL and narrow down the candidate regions (Han et al ). To date, GWAS was widely used to analyze a number of agronomic traits in maize, such as seedling root‐related traits (Pace et al ), stalk strength (Peiffer et al ), leaf architecture (Tian et al ), stalk cell wall components (Li et al ), plant and ear height (Li et al ), stalk lodging‐related traits (Zhang et al ), embryonic callus regenerative capacity (Ma et al ) and maize kernel size (Liu et al ). However, GWAS has not been applied to detect the associations with the length of ETB because of the hysteretic study on maize ETB.…”
Section: Introductionmentioning
confidence: 99%